Morphometric analysis of Rasyan valley basin - A case study in the Republic of Yemen, using Remote Sensing and GIS techniques - MULIKI , MOHAMMED MANSOOR AL; BASAVARAJAPPA, H. T. (MAUSAM, 2008)
Remote Sensing and GIS has given more importance for investigation of the geomorphological features based on the morphometric analysis duo to the diversity of data information by using digital map characters which help in moderating of data base information to get a different data like distance, area, point, line, polygon and qualitative data. This has decreased the errors which resulted by manual map sources. The main aim of this paper is the study of a morphometric analysis and characteristics of river basin area, basin shape, length, width and the ratio of length to the width, the ratio of rotation and circularity of the basin. It is also a study of relief characteristic, like slope and basin texture hypsometric curve. And also a study of drainage network characteristic like streams, stream order, length, drainage density, turn ratio, bifurcation ratio, weighted bifurcation ratio, type of drainage, and the relationship between all variables that mentioned above with rock types and structural movements of internal and external factors which are represented by relief, climate, soil, type of vegetation along with the human impact on the other hand. Results have been discussed for Rasyan valley basin in the Republic of Yemen using Landsat data.